Performance analysis of a biomass-fired cooling/power combined cycle (Ejector Refrigeration and Kalina cycle) - (:unkn) unknown (IEEE, 2019)
In this current study, a combined power/cooling cycle which is composed of a Kalina cycle and an ejector refrigeration cycle is analyzed. The combined cycle is fed by the heat derived from biomass which is a renewable substitute of fossil fuels in energy generation processes. Ejector refrigeration cycle is inserted into Kalina cycle for the purpose of energy recovery. Developed mathematical model for the analysis is given explicitly. A parametric analysis is carried out to show the effect of variation in evaporator temperature of refrigeration cycle on power production, refrigeration production and energetic (thermal) efficiency of the combined cycle. In order to determine the prevailing factors on overall energetic efficiency, efficiency of Kalina cycle and ejector refrigeration cycle are also obtained under the same operational conditions. It is seen that, combined power/refrigeration cycle thermal efficiency is overwhelmingly dominated by Kalina cycle thermal efficiency and Kalina cycle operational parameters must be preliminarily focused on to improve the overall efficiency of the combined power/cooling cycle.
Keywords: ejector refrigeration cycle; Kalina cycle; ejector; THERMODYNAMIC ANALYSIS; SYSTEM; POWER; WASTE